2021
DOI: 10.1097/rhu.0000000000001755
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk Assessment in Women With Rheumatoid Arthritis Through Carotid and Femoral Artery Doppler Ultrasound

Abstract: Objective:The aims of this study were to assess cardiovascular risk in patients with rheumatoid arthritis (RA) classified as low-risk by the Framingham score, before and after the multiplication by 1.5 recommended by the European League Against Rheumatism (EULAR), and to stratify them using carotid and femoral Doppler ultrasound (DUS) in order to optimize the assessment of the asymptomatic cardiovascular disease incidence.Methods: Thirty-five female patients with RA and 35 healthy women (control group), both w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…In a recent publication from Sacilotto et al ( 264 ), they found in a small cohort that the EULAR criteria are effective at identifying patients with high CV risk and that the Doppler ultrasound in carotids and femoral arteries are tools that can be used in clinical practice to detect CV disease even in their asymptomatic stage. In addition, Aceituno-Melgar et al ( 265 ) found Echo variables that were statistically significant in RA patients and served as early diagnosis of subclinical CV involvement, supporting that even those patients in low risk or even asymptomatic according to EULAR criteria would benefit from a deeper investigation of such involvement.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent publication from Sacilotto et al ( 264 ), they found in a small cohort that the EULAR criteria are effective at identifying patients with high CV risk and that the Doppler ultrasound in carotids and femoral arteries are tools that can be used in clinical practice to detect CV disease even in their asymptomatic stage. In addition, Aceituno-Melgar et al ( 265 ) found Echo variables that were statistically significant in RA patients and served as early diagnosis of subclinical CV involvement, supporting that even those patients in low risk or even asymptomatic according to EULAR criteria would benefit from a deeper investigation of such involvement.…”
Section: Discussionmentioning
confidence: 99%